Analogy and Authority in Cyberterrorism Discourse: An Analysis of Global News Media Coverage. Issue 4 (1st October 2016) - Jarvis, Lee; Macdonald, Stuart; Whiting, Andrew
Abstract : This article explores constructions of cyberterrorism within the global news media between 2008 and 2013. It begins by arguing that the preoccupation with questions of definition, threat and response in academic literature on cyberterrorism is problematic, for two reasons. First, because it neglects the constitutivity of representations of cyberterrorism in the news media and beyond; second, because it prioritises policy-relevant research. To address this, the article provides a discursive analysis drawing on original empirical research into 31 news media outlets across the world. Although there is genuine heterogeneity in representations of cyberterrorism therein, we argue that constructions of this threat rely heavily on two strategies. First, appeals to authoritative or expert "witnesses" and their institutional or epistemic credibility; second, generic or historical analogies, which help shape understanding of the likelihood and consequences of cyberterrorist attack. These strategies have particular discursive importance, we argue, given the lack of readily available empirical examples of the "reality" of cyberterrorism.